Triazolyl Ru(II), Os(II), and Ir(III) complexes as potential HIV-1 entry inhibitors - Gama, Ntombenhle Hlengiwe (University of Pretoria, 2021)
Dissertation (MSc (Biochemistry))--University of Pretoria, 2021.